2015
DOI: 10.1093/wber/lhv001
|View full text |Cite
|
Sign up to set email alerts
|

Deals and Delays: Firm-level Evidence on Corruption and Policy Implementation Times

Abstract: Whether demands for bribes for particular government services are associated with expedited or delayed policy implementation underlies debates around the role of corruption in private sector development. The "grease the wheels" hypothesis, which contends that bribes act as speed money, implies three testable predictions. First, on average, bribe requests should be negatively correlated with wait times. Second, this relationship should vary across firms, with those with the highest opportunity cost of waiting b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…To address these issues, we first use an alternative proxy, finance_country_sector_size , which is the mean (external finance use) of firms in the same country, industry and size class—a measure that is not polluted by firms’ idiosyncratic characteristics (Escribano & Guasch, 2005; Freund et al, 2016). Thus, we believe this proxy gets rid of the omitted variable bias resulting from unobservables that are correlated with a firm’s access to external finance.…”
Section: Resultsmentioning
confidence: 99%
“…To address these issues, we first use an alternative proxy, finance_country_sector_size , which is the mean (external finance use) of firms in the same country, industry and size class—a measure that is not polluted by firms’ idiosyncratic characteristics (Escribano & Guasch, 2005; Freund et al, 2016). Thus, we believe this proxy gets rid of the omitted variable bias resulting from unobservables that are correlated with a firm’s access to external finance.…”
Section: Resultsmentioning
confidence: 99%
“…But others (e.g. Freund, Hallward-Driemeier, and Rijkers, 2015) rejected the 'grease the wheel hypothesis' and found a strong negative association between bribe demands and firm growth. More recent meta-analyses of the existing studies on corruption, however, confirm a negative impact on growth xxi .…”
Section: Growth-governance Nexus: Review Of the Literaturementioning
confidence: 99%
“…Some analyses have found that rather than 'grease' transactions, bribes are extracted by officials who 'sand the wheels' of the provision of public services, and thus use delays to extract rents from firms (Kaufmann and Wei, 1999). In fact, such a delay-to-extract mechanism has been shown to operate across several types of transactions (Freund et al, 2016). These models can be loosely grouped under a category of "bureaucrat as gatekeeper", where firms actively seek a government service, such as a license or permit, and are thus exposed under certain conditions to a request for a bribe.…”
Section: Corruption and Informalitymentioning
confidence: 99%
“…sizesector-location) is calculated omitting the firm-level input (see, e.g. Freund et al, 2016); the measure of harass, called "harass donut", uses GPS data to provide a location-based structure of these measures. As such, it proxies an informal business's exposure to harassment.…”
Section: Main Econometric Specificationmentioning
confidence: 99%